Reading (and managing) blogs from mobile devices - Arroyo-Vázquez, Natalia (Anuario ThinkEPI, 2010)
Accessing the Web from mobile devices sometimes entails difficulties due to the technical and physical characteristics of these appliances. There are several methods for improving the reading of blogs on these devices: on the one hand, readers can use an aggregator; on the other hand, bloggers can use free online services, install plug-ins in the content management system or create new templates. These methods and others that help to manage blogs from mobile devices are explained.